The carotid body: a physiologically relevant germinal niche in the adult peripheral nervous system - Sobrino, V; Annese, V; Navarro-Guerrero, E; Platero-Luengo, A; Pardal, R (Springer, 2018)
Oxygen constitutes a vital element for the survival of every single cell in multicellular aerobic organisms like mammals. A complex homeostatic oxygen-sensing system has evolved in these organisms, including detectors and effectors, to guarantee a proper supply of the element to every cell. The carotid body represents the most important peripheral arterial chemoreceptor organ in mammals and informs about hypoxemic situations to the effectors at the brainstem cardiorespiratory centers. To optimize organismal adaptation to maintained hypoxemic situations, the carotid body has evolved containing a niche of adult tissue-specific stem cells with the capacity to differentiate into both neuronal and vascular cell types in response to hypoxia. These neurogenic and angiogenic processes are finely regulated by the niche and by hypoxia itself. Our recent data on the cellular and molecular mechanisms underlying the functioning of this niche might help to comprehend a variety of different diseases coursing with carotid body failure, and might also improve our capacity to use these stem cells for the treatment of neurological disease. Herein, we review those data about the recent characterization of the carotid body niche, focusing on the study of the phenotype and behavior of multipotent stem cells within the organ, comparing them with other well-documented neural stem cells within the adult nervous system.